Analisis Nilai-Nilai Pendidikan Moral dan Agama Anak Usia Dini dalam Kitab Kuning - Maisaroh, Maisaroh; Hikmah, Fitrotul (Sekolah Tinggi Agama Islam Al-Kifayah Riau, 2024)
This article analyzes the values ​​of moral and religious education for early childhood in kitab kuning. In this case, the book in question is At-Tahliyah Wat-Tarhib Fi At-Tarbiyah Wat-Tahdzib by KH. Sayyid Muhammad, then analyzed transliteration and the relevance of religious moral education for early childhood. Religious moral education is a form of instilling moral and religious values, therefore it is very important to give it from an early age because basically children are in a golden age which is experiencing a very rapid growth and development process. The book that is the focus of this research is one of the sources for religious moral education, because it discusses morals, moreover, in this book there are 13 chapters that discuss good morals towards oneself, towards family and social life. This research method uses a qualitative approach with library research methods. For data collection techniques, library studies, observation, documentation and data analysis techniques are used. As a result, there are 15 values ​​of religious moral education that can be used as a reference in the early childhood learning process, including good manners, caring for the body, protecting the rights of the body, morals towards parents, good character, honesty, shame, generous, restraining anger, obeying the government, listening to conversations, speech etiquette, keeping secrets, eating manners, and love of the country